IS EMPLOYEE PERFORMANCE INFLUENCED BY DISCIPLINE, MOTIVATION, AND COMPETENCE? A STUDY ON SALON AND BEAUTY EQUIPMENT BUSINESS - Manafe, Leonard Adrie; Wahib, Moh; Zebua, Martin; Andriana, Ririn; Erawati, Yourini (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The research conducted to know the discipline, motivation and competencies impacted on performance of employee at Evy Beautrec ("EB"). EB is a salon and beauty equipment manufacturer based in Surabaya. The study employed quantitative methods using saturated sampling/all respondents from the population are used as the research sample. The sample size was 33 people who are employees of EB. Data was collected by distributing questionnaires and conducting several interviews with the respondents. The methods used to analyze the data were multiple linear regression, which was processed using SPSS tool. The results of the research are confirmed by t-test calculations, which show that discipline, motivation and competence have a significant impact on EB employees’ performance respectively. Furthermore, the F-test results show that EB employees’ performance simultaneously impacted by discipline, motivation and competence. Of the three independent variables studied, motivation has the greatest effect on EB employees' performance, followed by competence and discipline. Previous findings have shown that still nothing variables that impacts on employees performance, and this phenomenon has attracted the interest of researchers to investigate the performance of EB employees in relation to the impacted by work discipline, motivation and competence.